2014
DOI: 10.1177/1088767914522466
|View full text |Cite
|
Sign up to set email alerts
|

How Do Kidnappers Kill Hostages? A Comparison of Terrorist and Criminal Groups

Abstract: This study explores how hostages are murdered during a kidnapping for ransom. A multi-dimensional scaling procedure was used to explore the homicidal behavior of kidnappers. Three styles of homicide, labeled as execution, manual, and slaughter, were identified. Each varied in the degree of expressive/instrumental aggression and planned or spontaneous violence. Classification of the sample data found that 46.4% of kidnapping homicides were characterized by instrumental violence labeled as execution style, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Common criminal groups were more likely to kill their victims spontaneously than organized criminals or terrorists. This finding suggests that the expertise of offenders may be predictive of victim outcomes (Phillips, 2015). Common criminal groups are less experienced in K&R than other groups and may act more impulsively while negotiating for ransom payments.…”
Section: Research Contextmentioning
confidence: 97%
See 4 more Smart Citations
“…Common criminal groups were more likely to kill their victims spontaneously than organized criminals or terrorists. This finding suggests that the expertise of offenders may be predictive of victim outcomes (Phillips, 2015). Common criminal groups are less experienced in K&R than other groups and may act more impulsively while negotiating for ransom payments.…”
Section: Research Contextmentioning
confidence: 97%
“…The findings revealed that specific forms of violence were predictive of outcomes while the type of group was not. In a similar study, Phillips (2015) investigated how ransomed victims were killed in captivity as a proxy measure for rationality. Evidence showed that about half of the victims died execution style and half were the product of spontaneous violence (i.e., generally killed without a weapon and more barbaric in nature).…”
Section: Research Contextmentioning
confidence: 99%
See 3 more Smart Citations